A Sustainable Philosophy-The Work of Bryan Norton (The International Library of Environmental, Agricultural and Food Ethics,, 2018)
This book provides a richly interdisciplinary assessment of the thought and work of Bryan Norton, one of most innovative and influential environmental philosophers of the past thirty years. In landmark works such as Toward Unity Among Environmentalists and Sustainability: A Philosophy of Adaptive Ecosystem Management, Norton charted a new and highly productive course for an applied environmental philosophy, one fully engaged with the natural and social sciences as well as the management professions. A Sustainable Philosophy gathers together a distinguished group of scholars and professionals from a wide array of fields (including environmental philosophy, natural resource management, environmental economics, law, and public policy) to engage Norton's work and its legacy for our shared environmental future. A study in the power of intellectual legacy and the real-world influence of philosophy, the book will be of great interest scholars and students in environmental philosophy, public policy and management, and environmental and sustainability studies. By considering the value and impact of Norton's body of work it will also chart a course for the next generation of pragmatic environmental philosophers and sustainability scholars grappling with questions of environmental value, knowledge, and practice in a rapidly changing world.